MOTIVASI AKADEMIK DAN LINGKUNGAN PEMBELAJARAN DARING SEBAGAI PREDIKTOR PRESTASI AKADEMIK MAHASISWA - Muhammad Rizkyanto; Sri Lestari (Program Studi S1 Psikologi, 2023)
Online learning, carried out during the Covid-19 pandemic, forced students to study from home, causing complaints of a lack of enthusiasm for learning. The online learning environment as a new learning environment for students is different from the learning environment in class when offline. This study examines the effect of academic motivation and the online learning environment on student academic achievement. This study used a quantitative approach involving 218 students from private tertiary institutions who were caught using the accidental sampling technique. Data collection was carried out using two scales which were circulated online in the form of a Google form. Respondents were also asked to include results of academic achievement. The data obtained were analyzed using multiple linear regression analysis techniques. The study results show that academic motivation and the online learning environment can simultaneously predict student academic achievement. Separately, only academic motivation influences student academic achievement. This research implies that growing and maintaining student academic motivation can help students deal with different learning situations to achieve their academic achievement.